(untitled) (Research, Society and Development, 2021)
Aim: To analyze the mechanical efficiency of kick kicking in order to identify if physiological wear can influence the performance of the technical gesture during a combat. Methods: Two practitioners participated in the study. Only one was analyzed the other participated only in the phase of the combat simulation. The research was performed in two phases, starting with the progressive treadmill test for the identification of lactate thresholds and heart rate. Blood samples from the earlobe were collected at rest and during the test at the end of each increment. The second phase was the combat simulation for the identification of physiological and biomechanical changes resulting from each round, as well as Subjective Effort Perception (PSE). Results: High correlations were found between maximal angle, range of motion and percentage of fatigue with the physiological variables of PSE and lactate concentration during the fight, a similarity was observed in the angular kinematic pattern of the analyzed segments, there was a decrease in the values ​​of each round when compared to the resting value, as well as in relation to the range of motion. Conclusion: Physiological wear encountered during rounds in a Kickboxing match can influence the maximum angulation and range of motion of the front kick with jump.